Co‐Intercalation Batteries (CoIBs): Role of TiS2 as Electrode for Storing Solvated Na Ions. Issue 47 (21st October 2022) - Alvarez Ferrero, Guillermo; Åvall, Gustav; Mazzio, Katherine A.; Son, Youhyun; Janßen, Knut; Risse, Sebastian; Adelhelm, Philipp
Abstract: The co‐intercalation of solvent molecules along with Na + into the crystal lattice of electrode materials is an undesired process in sodium batteries. An exception is the intercalation of ether solvated alkali ions into graphite, a fast and highly reversible process. Here, reversible co‐intercalation is shown to also be possible for other layered materials, namely titanium disulfide. Operando X‐ray diffraction and dilatometry are used to demonstrate different storage mechanisms for different electrolyte solvents. Diglyme is found to co‐intercalate into the TiS2 leading to a change in the voltage profile and an increase in the interlayer spacing (≈150%). This behavior is different compared to other solvents, which expand much less during Na storage (24% for tetrahydrofuran [THF] and for a carbonate mixture). For all solvents, specific capacities (2nd cycle) exceed 250 mAh g −1 whereas THF exhibited the best stability after 100 cycles. The solvent co‐intercalation is rationalized by density functional theory and linked to the stability of the solvation shells, which is largest for diglyme. Finally, the TiS2 electrode with diglyme electrolyte is paired with a graphite electrode to realize the first proof‐of‐concept solvent co‐intercalation battery, that is, a battery with two electrodes that both rely on reversible co‐intercalation of solvent molecules. Abstract : Reversible co‐intercalation of diglyme with Na + is demonstrated for layered titanium disulfide with a higher lattice expansion than tetrahydrofuran and a carbonate mixture. The first proof‐of‐concept solvent co‐intercalation battery is assembled in diglyme electrolyte with TiS2 and graphite electrodes, both operating on reversible co‐intercalation mechanism of solvent molecules.